The practical guide to managing nonprofit assets - Schneider, William A. (Wiley, 2005)
From modern portfolio theory to the role of the fiduciary, The Practical Guide to Managing Nonprofit Assets provides trustees of nonprofit funds with a chapter-by-chapter explanation of what they should know to carry out their responsibilities. For the uninitiated, it creates a foundation for understanding investing in a difficult environment. For the experienced, it serves as a checklist of issues to be considered in exercising appropriate investment oversight